KOMPARASI PENGGUNAAN WALLPAPER DAN PENGECATAN PADA DINDING INTERIOR GEDUNG (STUDI KASUS : HOTEL GRASIA SEMARANG) - Suci Zulaikhah; Gumilang Ilham Pratama; Garup Lambang Goro; Suwarto Suwarto (Politeknik Negeri Semarang, 2022)
Recently, the use of wallpaper and paint as a coating wall was in great demand. Wall coating was not only for the room’s aesthetics but was also used to keep the temperature of the room. The objective of this study is to determine the effect of wall coating type on the temperature's room comfort, specifically to know about the effect of using wallpaper and wall paint for the temperature of the room. The study also aims to compare the construction cost of using both materials. Temperature measurements in the room area consider to the occupant time activities, i.e. 6.00 am to 8.00 pm, it was measured on a grid with interval distance of 2m and elevation of 0,5m, 1m, 1,5, and 2m. The results of the comparison conclude that the wallpaper's wall is more stable for keep temperature of the room, but painted wall gives the effect of inside room more cooling. The Budget Plan (RAB) for setting up wallpaper was more expensive i.e. Rp. 180,965.00 per m2 than the cost of wall painting wall of Rp. 67,577.00 per m2. The Implementation Cost (RAP) was of using wallpaper also more expensive of Rp. 142,469.00 per m2 than wall painting is Rp. 58,383.00 per m2.